PENYULUHAN DAN PENDAMPINGAN PADA KORBAN SELAMAT PERCOBAN BUNUH DIRI DI GUNUNG KIDUL - Tentama, Fatwa; Mulasari, Surahma Asti; Sukesi, Tri Wahyuni; Sulistyawati, Sulistyawati (Universitas Pendidikan Ganesha, 2019)
Suicide is a global problem. According to the WHO in 2015 more than 800,000 people / year died from suicide. The average number of Indonesians who died from suicide reached 24 per 100,000 inhabitants. at present the suicide case in Gunungkidul shifts to productive age. The increase in suicides in Gunungkidul is a problem that must be dealt with together. The purpose of this activity is to increase knowledge, and mental health for survivors, families, and communities in Gunungkidul and to prevent rising suicide rates in Gunungkidul. The method applied in this activity is counseling and mentoring. The impact gained is an increase in family and community knowledge about endurance and the role that can be taken in preventing suicide in the surrounding environment, in addition it is expected to restore psychological and spiritual pressure to the victim so as not to commit suicide again.